The Effect of Scan Length on the Assessment of BOLD Delay in Ischemic Stroke - Tanrıtanır, Ayse Ceren; Villringer, Kersten; Galinovic, Ivana; Grittner, Ulrike; Kirilina, Evgeniya; Fiebach, Jochen B.; Villringer, Arno; Khalil, Ahmed A. (Frontiers in Neurology, 2020)
To evaluate the impact of resting-state functional MRI scan length on the diagnostic accuracy, image quality and lesion volume estimation of BOLD delay maps used for brain perfusion assessment in acute ischemic stroke. Sixty-three acute ischemic stroke patients received a 340 second resting-state functional MRI within 24 hours of stroke symptom onset. BOLD delay maps were calculated from the full scan and four shortened versions (68s, 136s, 204s, 272s). The BOLD delay lesions on these maps were compared in terms of spatial overlap and volumetric agreement with the lesions derived from the full scans and with time-to-maximum (Tmax) lesions derived from DSC-MRI in a subset of patients (n=10). In addition, the interpretability and quality of these maps were compared across different scan lengths using mixed models. Shortened BOLD delay scans showed a small volumetric bias (ranging from 0.05 to 5.3 mL; between a 0.13% volumetric underestimation and a 7.7% overestimation relative to the mean of the volumes, depending on scan length) compared to the full scan. Decreased scan length was associated with decreased spatial overlap with both the BOLD delay lesions derived from the full scans and with Tmax lesions. Only the two shortest scan lengths (68 s and 136 s) were associated with substantially decreased interpretability, decreased structure clarity, and increased noisiness of BOLD delay maps. BOLD delay maps derived from resting-state fMRI scans lasting 272 s and 204 s provide sufficient diagnostic quality and adequate assessment of perfusion lesion volumes. Such shortened scans may be helpful in situations where quick clinical decisions need to be made.